The Effects of Marketing Mix Elements on Customer-Based Brand Equity in Retailing - , Yohanes Hans Ananda, Prof. Dr. Basu Swastha Dhammesta, M.B.A. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Nowadays many retail companies cannot survive in this high competitive era. Even more many multinational retail companies come into Indonesia, because they look Indonesia as a potential market. This situation makes retail industry in Indonesia more competitive. One important factor that can make retail companies survive from this high competition era is brand equity of the store. Any marketing efforts will affect brand equity positively when they lead to more favorable behavioral responses to the focal products than to the equivalent unbranded products. Managerial efforts embedded in controllable marketing action are related to brand equity through the mediation of the dimensions of brand equity. Therefore to build strong brand equity, it is very important to know the effect of marketing efforts in marketing mix elements to the dimensions of brand equity. This research uses value/price ratio, distribution intensity, advertising, sponsorship, store service, and price deals as marketing mix elements. Based on Kellerâs model, this research uses brand image and brand awareness as mediating variable because they are the dimensions of brand equity. 180 questionnaires were distributed in 18 Indomaret. The results of this research are distribution intensity and advertising affect brand awareness positively and value/price ratio, advertising, store service, and price deals affect brand image positively. Then brand awareness and brand image simultaneously affect brand equity positively.